Prevalence and characteristics of dyspepsia among college students in Zhejiang Province - Li, Meng (Baishideng Publishing Group Co., Limited, 2014)
AIM: To investigate the prevalence and characteristics of uninvestigated dyspepsia among college students in Zhejiang Province. METHODS: Young adult students attending undergraduate (within the 4-year program) and graduate (only first-year students) colleges in Zhejiang Province were recruited between November 2010 and March 2011 to participate in the self-report survey study. The questionnaire was designed to collect data regarding demographics (sex and age), general health [weight and height, to calculate body mass index (BMI)], and physical episodes related to gastrointestinal disorders. Diagnosis of dyspepsia and irritable bowel syndrome (IBS) was made according to the Rome III criteria. Gastroesophageal reflux disease (GERD) was defined by episodes of heartburn and/or acid reflux that occurred at least once a week, according to the Montreal definition. RESULTS: Of 2520 students recruited for survey participation, only 1870 (males: 967; age range: 17-32 years, mean age: 21.3 years) returned a completed questionnaire. One hundred and eight (5.67%) of the student participants fit the criteria for dyspepsia diagnosis. Stratification analysis of dyspepsia and non-dyspepsia cases showed no statistically significant differences in age or BMI; however, the prevalence of dyspepsia was significantly higher in women than in men (7.53% vs 4.14%, P < 0.05). Stratification analysis of dyspepsia by grade level showed that year 4 undergraduate students had a significantly higher prevalence of dyspepsia (10.00% vs undergraduate year 1: 5.87%, year 2: 3.53% and year 3: 7.24%, and graduate year 1: 3.32%). Nearly all (95.37%) students with dyspepsia reported symptoms of postprandial distress syndrome, but only a small portion (4.63%) reported symptoms suggestive of abdominal pain syndrome. The students with dyspepsia also showed significantly higher rates of IBS (16.67% vs non-dyspepsia students: 6.30%, P < 0.05) and GERD (11.11% vs 0.28%, P < 0.05). CONCLUSION: Although the prevalence of dyspepsia among Zhejiang college students is low, the significantly higher rates of concomitant IBS and GERD suggest common pathophysiological disturbances.